2014
DOI: 10.1155/2014/904657
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mesomorphic Properties of New Fluorinated Schiff Base Liquid Crystals

Abstract: Two new compounds, 4-alkanoyloxybenzylidene-4 -fluoroaniline and 4-fluorobenzylidene-4 -n-alkanoyloxyaniline comprising a terminal fluorosubstituent were studied. The fluoro substituent contributes to the molecular polarizability, thus affecting intermolecular interactions and hence resulting in smectic mesomorphism. The mesomorphic properties were studied using differential scanning calorimetry and polarizing optical microscopy techniques. The mesomorphic properties of compounds studied are strongly dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Saccone et al suggested that on changing the degree of fluorination, the fine tuning of temperature is possible over a mesomorphic range [23]. Phillips and Pombeiro, and others have reported that the addition of halogen atom in a drug molecule may increase its liophilicity and also the addition of halogen atom induces strong dipole moment within the liquid crystal and these results in the enhancement of lattice stability [24][25][26][27]. This also increases the ionic radius of the molecule and makes it more parallel in the alignment within an electrode [28].…”
Section: Introductionmentioning
confidence: 99%
“…Saccone et al suggested that on changing the degree of fluorination, the fine tuning of temperature is possible over a mesomorphic range [23]. Phillips and Pombeiro, and others have reported that the addition of halogen atom in a drug molecule may increase its liophilicity and also the addition of halogen atom induces strong dipole moment within the liquid crystal and these results in the enhancement of lattice stability [24][25][26][27]. This also increases the ionic radius of the molecule and makes it more parallel in the alignment within an electrode [28].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in [13] that the dipole moment of the mesomeric portion of the molecule impacts the type and stability of the mesophase produced, which is dependent on the attached terminal polar substituent and the steric one that varies according to size. The halogen substituent at the terminal position showed strong influence on the mesomorphic behavior of the Schiff base molecules [30]. In our present study, the halogenated compound C (X = I) is dimorphic, with the highest thermal nematic stability (182.0 °C) and SmA stability (136.3 °C).…”
Section: Resultsmentioning
confidence: 53%
“…Halogen (F, Cl, Br) groups at the terminal position showed strong impact on the mesomorphic properties of a molecule. The melting and transitions temperatures of current compound, 8BrBA are higher than those of 8FBA [39] and 8ClBA [40]. The size of bromine atom is larger in comparison with fluorine and chlorine atoms and the electrons on the bromine atom are loosely held and far from the nucleus.…”
Section: Methodsmentioning
confidence: 81%
“…Molecular structure of organic compounds and their liquid crystalline properties are closely correlated. Table 2 lists the transition temperatures and mesomorphic behaviors of 8BrBA and structurally related compounds [25,[39][40][41].…”
Section: Methodsmentioning
confidence: 99%